Channel-aware inter-slice scheduling for SLA assurance: theoretical and simulation-based approaches - Silva, Daniel Campos da (2025)
As the diversity of applications with heterogeneous Quality of Service (QoS) requirements grows in mobile networks, network slicing emerges as a key technology to meet Service Level Agreements (SLAs) by isolating resources among different types of services grouped into independent slices. Efficient inter-slice radio resource scheduling (RRS) is crucial in this context, directly governing the achievable throughput - and thus SLA assurance - while also enabling energy efficiency gains in low-demand scenarios through reduced resource usage and power consumption in the base station. This thesis investigates high-performance inter-slice RRS characteristics, including channelawareness, intra-slice RRS prediction, SLA-drift-oriented allocation, dynamic slice resource proportions, and fairness among users within the same slice. We formulate the RRS problem mathematically, facilitating the design of RRS heuristics approximating optimal solutions. Through simulations, we demonstrate how our proposed algorithms outperform state-of-the-art schedulers in both SLA assurance and resource efficiency.